Teknologi Augmented Reality Di Era 5.0 untuk Meningkatkan Pengetahuan dan Konsentrasi Peserta Didik Tingkat SMP Pada Pembelajaran PJOK - Ariestika, Elsa; Amni, Hazrina; Sari, Nugrahani Febrina; Wulandari, Indri (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
This study aims to increase the knowledge and concentration of junior high school students in PJOK learning with augmented reality technology. This study uses a quantitative approach method with an experimental design